Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Let $T$ be an exponential random variable with PMF $P_T(t) = \lambda e^{-\lambda t}$.

I am trying to show that after an arbitrary time $k$, the random variable $T - k$ is still exponential with parameter $\lambda$.

Here is my attempt.

$P(T \le t) = 1 - e^{-\lambda t}$, so $$P(T - k \le t | T > k) = \frac{P(T \le t + k)P(k < T \le t + k)}{P(T > k)}.$$

Computing these probabilities seperately, I get $$P(T \le t + k) = 1 - e^{-\lambda(t + k)}$$ $$P(k < T \le t + k) = P(T \le t + k) - P(T \le k) = e^{-\lambda k} - e^{-\lambda (t + k)} = e^{-\lambda k}(1 - e^{-\lambda t})$$ $$P(k > T) = 1 - P(T \le k) = 1 - (1 - e^{-\lambda k}) = e^{-\lambda k}$$

Therefore, plugging in we get, $$P(T - k \le t | T > k) = (1 - e^{-\lambda(t + k)})(1 - e^{-\lambda t}).$$

My expectation was that $P(T - k \le t| T > k) = 1 - e^{-\lambda t}$.

Can anyone explain where I went wrong? Or why my expectation is wrong?

share|cite|improve this question
ah, just wrote this out on paper with arbitrary events A and B. And now I feel stupid. Thanks... heh – zrbecker Mar 19 '13 at 16:11
up vote 2 down vote accepted

$$P(T-k\leq t\mid T>k)=\frac{P(T\leq t+k,\, T>k)}{P(T>k)}.$$ In other words, the numerator is $P(\{T\leq t+k\}\cap \{T>k\})$ which just corresponds to the second probability.

share|cite|improve this answer
thanks, my brain is fried. heh – zrbecker Mar 19 '13 at 16:16
Hehe, you're welcome :) – Stefan Hansen Mar 19 '13 at 16:32

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.